Cytotoxicity activity of biotransformed ethyl p-methoxycinnamate by Aspergillus niger - Omar, Muhammad Nor; Hasali, Nor Hazwani; Yarmo, Mohd Ambar (Oriental Scientific Publishing Company, 2016)
The extraction of Kaempferia galanga rhizome using steam distillation and supercritical fluid extraction (SFE) was carried out. After fractionation, the major compound of the K. galanga extract, ethyl p-methoxycinnamate (EPMC) was transformed using Aspergillus niger into ethyl p-hydroxycinnamate (EPHC). The biological anticancer activity of EPMC and its biotransformed product (EPHC) was established by cytotoxicity activity on the human breast cancer (MCF-7) cell line using MTT assay. Ethyl p-hydroxycinnamate (EPHC) was most cytotoxic against MCF-7 at 1000 μg/mL where percentage of cell viability was 9.87 %, while IC50 was 340 μg/mL. EPHC showed slightly higher cytotoxicity activity compared to EPMC. The results of this study show that the biotransformation process was able to produce a metabolite (EPHC) with higher cytotoxicity activity compared to its parent compound (EPMC).